2012
DOI: 10.1007/s11552-012-9470-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes for Kienböck's Disease

Abstract: Background The precise etiology of Kienböck's disease is unclear. Controversy exists regarding the appropriate treatment modality. The present study sought to investigate and compare surgical and nonsurgical treatment outcomes of patients suffering from Kienböck's disease in the province of Newfoundland and Labrador (NL), Canada. Methods The present study was a retrospective analysis of 66 patients. The primary outcome was the Disabilities of the Arm, Shoulder, and Hand (DASH) score. Student's t test was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Although there is no consensus on the subject of treatment, surgical treatment is recommended for symptomatic patients. 4 Surgical methods that decrease the load on the lunatum and biological methods that provide revascularization and salvage operations have all been reported. In literature, a significant increase in functional scores has been obtained after surgical treatment regardless of the surgical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no consensus on the subject of treatment, surgical treatment is recommended for symptomatic patients. 4 Surgical methods that decrease the load on the lunatum and biological methods that provide revascularization and salvage operations have all been reported. In literature, a significant increase in functional scores has been obtained after surgical treatment regardless of the surgical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Six studies also found that patients symptoms can improve with non-operative treatment [8,[13][14][15][16][17]. Symptoms were not correlated with stage of disease or its progression in five studies [15,[17][18][19][20]. The radiographic osseous architecture of the lunate was found to improve in some patients with non-operative treatment in three studies [16,17,21].…”
Section: Resultsmentioning
confidence: 99%
“…If revascularization and healing do not occur, Kienböck's can progress with either operative or non-operative treatment [15][16][17][18][19]. Many studies found that though this progression does occur, patients' symptoms can improve or stabilize with non-operative treatment [17][18][19][20][21]. Furthermore, symptoms are not necessarily correlated with the stage of disease or its progression [16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…23 It is important to note that some studies have indicated that the clinical symptoms of Kienböck disease do not necessarily progress in all patients. 2 Therefore, at this point, indications for surgical intervention should only be based on patients' symptoms and functional impairment, and not on radiographic evidence. 2 In our study, we identified cartilage health to be a determinant factor of clinical outcomes, with patients having mild or no cartilage damage achieving a better recovery of grip strength, postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…2 Therefore, at this point, indications for surgical intervention should only be based on patients' symptoms and functional impairment, and not on radiographic evidence. 2 In our study, we identified cartilage health to be a determinant factor of clinical outcomes, with patients having mild or no cartilage damage achieving a better recovery of grip strength, postoperatively. Once the articular cartilage has deteriorated, full recovery will not occur, which explains why the severity of cartilage lesions affects clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%